Comparison Analysis of the Effectiveness of Three Microcontroller Practicum Media (Trainer-Box, Simulation Software, and Breadboard Hands-On) at SMK Negeri 1 Sentani - Oktaviani, Theresia Wuri; Suparno, Suparno; Samma, Lantik; Tampubolon, Aloysius; Yarangga, Vanderi Agus (Universitas Syiah Kuala, 2025)
Microcontroller practicum learning in Vocational High Schools (SMK) requires effective media to help students understand both concepts and practical skills optimally. This study aims to analyze the comparison of the effectiveness of three microcontroller practicum media, namely trainer-box, simulation software, and breadboard hands-on, in improving student learning outcomes. The research was conducted using a quasi-experimental method on 14 students from class XI at SMK Negeri 1 Sentani, majoring in Industrial Electronics. The instruments used were a pretest and posttest consisting of 20 multiple-choice questions, along with a student satisfaction questionnaire with 12 Likert scale questions. The analysis results show that the average pretest score of 52.143 increased to 71.786 in the posttest. The N-Gain calculation resulted in a value of 0.41, which falls into the moderate category, indicating that the use of all three media was effective in improving student learning outcomes. Based on the questionnaire results, student responses to the practicum media varied. The trainer-box received the highest average score (4.43, categorized as very high), followed by the breadboard hands-on (4.14, categorized as high), and lastly, the simulation software (3.36, categorized as moderate).